2020
DOI: 10.1177/1934578x20953951
|View full text |Cite
|
Sign up to set email alerts
|

Rutin as a Promising Inhibitor of Main Protease and Other Protein Targets of COVID-19: In Silico Study

Abstract: The process of investigating a possible cure for coronavirus disease 2019 (COVID-19) in vitro and in vivo may take a long time. For this reason, several in silico studies were performed in order to produce preliminary results that could lead to treatment. Extract of Juniperus procera Hochst is used as a traditional medicine for recovery from flu in Saudi Arabia. In the present study, more than 51 phytochemicals of J. procera were docked against the main protease of COVID-19. Rutin gave the highest interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Consistent with the results obtained in this work, rutin has been reported to show antimicrobial activity [92] and, through in silico studies, possible inhibitory activity of several proteins that are essential for SARS-CoV-2 to complete its viral cycle, [86] , [88] , [89] , [93] , [94] . However, its antiviral spectrom is broader and it is being tested experimentally as an antiviral agent against retroviruses, orthomyxoviruses, herpes viruses, hepatitis B and C viruses, and the H1N1 influenza virus.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with the results obtained in this work, rutin has been reported to show antimicrobial activity [92] and, through in silico studies, possible inhibitory activity of several proteins that are essential for SARS-CoV-2 to complete its viral cycle, [86] , [88] , [89] , [93] , [94] . However, its antiviral spectrom is broader and it is being tested experimentally as an antiviral agent against retroviruses, orthomyxoviruses, herpes viruses, hepatitis B and C viruses, and the H1N1 influenza virus.…”
Section: Resultssupporting
confidence: 91%
“…We also performed docking studies on lopinavir and Remdesivir as comparative standards. Moreover, we calculated the binding energy of phytochemical rutin found as the promising inhibitor of SARS-CoV-2 Mpro ( Al-Zahrani 2020 ). The calculated binding energy values are enlisted in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…QRK optimization parameters were obtained as 200 bar pressure, 35 °C temperature, 0.30 mm particle size and 3 l/min CO 2 flow rate, 8% w/w co-solvent ratio, and 120-min extraction period. There are scientific studies showing that rutin is more effective than lopinavir, which is used as a drug against COVID 19 virus (Al-Zahrani 2020 ). The rutin content of Pinus brutia pinecone was found by Soxhlet and Sc-CO 2 methods as 57.19 ± 3.81 µg/g and 14.75 ± 1.08 µg/g, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rutin (vitamin P) was reported to be a compound that inhibits the viability of ovarian cancer cells and induces apoptosis by endoplasmic reticulum stress signaling pathways (Zhao et al 2017 ). In a current silico study, it has been shown that rutin can be used more successfully in the treatment of Covid 19 by inhibiting the main protease on the surface of the COVID 19 virus (Al-Zahrani 2020 ). Quercetin has been identified as the most active flavonoid.…”
Section: Introductionmentioning
confidence: 99%